TINJAUAN YURIDIS PERKAWINAN ANTARA MASYARAKAT ADAT BADUY DALAM DENGAN MASYARAKAT ADAT BADUY LUAR: Juridical Review of Marriage Between The Inner Baduy Indigenous Community and The Outer Baduy Indigenous Community - Destiamara; Ning Adiasih (AMICUS CURIAE, 2025)
The term marriage in Baduy society is called Rukun Hirup, where if marriage is not carried out, then a person is considered to have violated his or her nature as a human. There are two marriage processes, namely Inner Baduy and Outer Baduy. The marriage process of the Baduy Dalam community still involves matchmaking and is followed by three stages of application. However, the identification problem is not on the marriage process, but on how to deal with marriages between the Inner Baduy and Outer Baduy communities. This research was conducted to answer the main problem, namely what is the practice of marriage between the Inner Baduy and Outer Baduy communities, and what are the legal consequences of this marriage. This research uses empirical legal research which is supported by empirical data with qualitative data management using nonprobability sampling techniques with accidental sampling methods, and conclusions are drawn deductively. The results and conclusiom of the research show that marriage practices between the Inner Baduy and Outer Baduy communities follow the implementation rules of the Outer Baduy. In the marriage between the two, there are legal consequences for the Inner Baduy community, namely that they have to leave and change their status to become Outer Baduy citizens.